A 3D geological model and cutting algorithm based on a vertically projected triangulated network. (October 2020) - Zhou, Cuiying; Du, Zichun; Ouyang, Jinwu; Zhang, Zhilong; Liu, Zhen
Abstract: Displaying 3D geological models and performing corresponding analyses in web browsers are trends in "smart city" development, but these tasks are often limited by the web browser and network transmission; therefore, large quantities of data cannot be quickly displayed or analysed, thereby constraining 3D geological models implemented in web browsers. The data redundancy and computational complexity of 3D geological models must be urgently optimized. Because of the data structure, it is difficult to further optimize the data redundancy and computational complexity of the current commonly used triangular prism (TP) model. If the model is sufficiently large, it can be difficult to display and analyse information in a web browser. Therefore, a new data structure and algorithm are necessary to optimize the data and number of calculations in 3D geological models. Thus, this paper uses a two-dimensional projection to simplify the data and proposes a new data structure for a 3D geological model based on a vertically projected triangulated network (VPTN) to describe the TP model. Based on the vertical sides of a TP, the horizontal coordinates and topology of the 3D model can be recorded by a 2D vertically projected triangulated network. According to the new data structure, this paper proposes a corresponding cutting algorithm that takes advantage of a VPTN to increase the computational speed. The VPTN model and TP model of a city in eastern China are built. The comparison of the modelling and cutting results of the two models is carried out, and the results show that the VPTN model can completely record the spatial coordinate information and topological information of the 3D geological model, reduce the memory space occupied by the model and decrease the number of calculations. The research results meet the needs of rapidly displaying 3D geological models and performing related analyses with a large data volume in web browsers. Moreover, these findings provide a reference for further optimization of 3D geological models. Highlights: The data structure of VPTN model can record the 3D model by a 2D network. The data structure of VPTN model can decrease the data volume of model. The cutting algorithm can reduce the calculations in the cutting process.